Forensic neuropsychological assessment: a review of its scope (Archives of Clinical Psychiatry, 2015)
Background Issues related to the field of mental health and justice require a multifactorial understanding of the possible causes of such issues. Objective To conduct an integrative literature review of controlled studies describing forensic neuropsychological assessment. Methods The articles were compiled and analyzed in two phases: 1) first, we retrieved all papers in PubMed by the keywords “Forensic Neuropsychology” and generated a growth curve for the subject and a cluster-based thematic distribution of publications. 2) We then conducted a curated analysis of all relevant papers indexed in Medline, PubMed and ISI, between 2000 and 2012. Results The evolution of the field during the last 15 years reveals an unstable growth pattern and three main thematic clusters. In terms of our curated analysis, a total of 390 articles were pre-selected, resulting in the selection of 44 fully-relevant studies, which comprise four main categories: cognitive damage in forensic psychiatric patients; imitation of cognitive damage; civil capacity, penal liability and violence risk; and validation of neuropsychological assessment tools. Discussion Two aspects appeared as the most relevant in this study: growth in the use of neuropsychological assessment as a diagnostic tool in the forensic context; and the necessity to enhance conformity in assessments.